Electroporation to Deliver Plasmid DNA into Rat Dental Tissues - Yao, Shaomian (2010)
BACKGROUND: Delivery of DNA into the target tissues is an important technique in gene function studies and gene therapy. Surgical treatment of tooth eruption disorders, such as impacted third molars, is a major health care cost. Because the dental follicle (DF) is essential for regulating tooth eruption, establishment of local gene transfer protocols is needed to determine the effect of various genes on eruption and to develop gene therapy approaches to induce the eruption of impacted molars. METHODS: Plasmids containing lacZ reporter gene were injected into rat mandibles and then electroporated at the designated settings. Mandibles were collected 24 hours after electroporation for X-gal staining to evaluate the transfection efficiency. Tissues were collected at various days post-electroporation to determine the expression of the transgene. RESULTS: For the DF, depth of injection and pulse number appear to be important. Six pulses can achieve above 80% transfection of the DF at 50V or 120V. For AB transfection, voltages are important with 120V being optimal. Regarding pulse durations, we determined that durations of 20 ms and 30 ms achieve the maximum transfection in AB and DF, respectively. CONCLUSIONS: This study demonstrates for the first time the feasibility of electroporation to locally deliver plasmids into dental tissues. Parameters affecting electroporation to deliver plasmids into the dental tissues were optimized. This protocol could be used to deliver shRNA or genes of interest into the dental tissues to regulate tooth eruption. Thus, it may be possible to develop non-surgical treatments for inducing eruption of impacted teeth.